A Clock Synchronization Strategy for Minimizing Clock Variance at Runtime in High-End Computing Environments - Jones, Terry; Koenig, Gregory A. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2010)
We present a new software-based clock synchronization scheme that provides high precision time agreement among distributed memory nodes. The technique is designed to minimize variance from a reference chimer during runtime and with minimal time-request latency. Our scheme permits initial unbounded variations in time and corrects both slow and fast chimers (clock skew). An implementation developed within the context of the MPI message passing interface is described and time coordination measurements are presented. Among our results, the mean time variance among a set of nodes improved from 20.0 milliseconds under standard Network Time Protocol (NTP) to 2.29 μsecs under our scheme.